Histoire et histoires dans la métropole québécoise: le quartier Côte-des-Neiges - Ramirez, Bruno (Le quartier Côte-des-Neiges à Montréal. Les interfaces de la pluriethnicité, 1997)
Keywords: Côte-des-Neiges; Quartiers

Les quartiers de la grande bourgeoisie: le cas du Golden Square Mile à Montréal - Bérubé, Harold (Histoire des villes nord-américaines, 2022)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Habiter un nouveau quartier ouvrier de la banlieue de Montréal; village Saint-Augustin (Municipalité de Saint-Henri) 1855-1881 - Lauzon, Gilles (Université du Québec à Montréal, 1986)
Keywords: Logement; Quartiers; Saint-Augustin; Saint-Henri

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

La Vita e bella - Létourneau, Isabelle (Continuité, 2001)
Keywords: Petite-Italie (quartier); Quartiers

Fighting from Home. The Second World War in Verdun, Quebec - Durflinger, Serge Marc (Studies in Canadian Military History Series, 2006)
Keywords: Guerre; Quartiers; Verdun

An Irish heart: how a small immigrant community shaped Canada - Doyle Driedger, Sharon (HarperCollins Publishers, 2011)
Keywords: Griffintown; Irlandais; Quartiers

Proprety and Power: Connecting the Dots - Olson, Sherry (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

L'attitude du clergé face aux changements occasionnés par l'industrialisation - Roy, Pierre-Georges (Montréal: activités, habitants, quartiers, 1984)

The Square Mile: Merchant Princes of Montreal - Mackay, Donald (Douglas & McIntyre, 1986)
Keywords: Bourgeoisie; Golden Square Mile; Marchands

Les débuts du diocèse - Litalien, Rolland (L'Église de Montréal, aperçus d'hier et d'aujourd'hui, 1836-1986, 1986)
Keywords: Diocèse

Esquisse géographique du territoire diocésain de Montréal, 1820-1852 - Remiggi, Frank W. (L'Église de Montréal, aperçus d'hier et d'aujourd'hui, 1836-1986, 1986)
Keywords: Diocèse

La société paroissiale en milieu urbain: Saint-Pierre-Apôtre de Montréal, 1848-1930 - Ferretti, Lucia (Université du Québec à Montréal, 1990)
Keywords: Communautés religieuses; Oblats de Marie-Immaculée; Saint-Pierre-Apôtre (paroisse)

Cadre paroissial et vie sociale urbaine: l'évolution de la paroisse Saint-Pierre-Apôtre de Montréal, 1850-1930 - Ferretti, Lucia (Études canadiennes / Canadian Studies, 1990)
Keywords: Communautés religieuses; Oblats de Marie-Immaculée; Saint-Pierre-Apôtre (paroisse)

L'école d'antan (1860-1960). Découvrir et se souvenir de l'école du Québec - Cadotte, Robert; Meunier, Anik (Presses de l'Université du Québec, 2011)
Keywords: Communautés religieuses; Enseignants; Étudiants

La paroisse urbaine comme communauté sociale: l'exemple de Saint-Pierre-Apôtre de Montréal, 1848-1930 - Ferretti, Lucia (La paroisse, 2001)
Keywords: Communautés religieuses; Oblats de Marie-Immaculée; Saint-Pierre-Apôtre (paroisse)

Les Madelinots à Verdun - Carbonneau, Pauline (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2005)
Keywords: Quartiers; Verdun

Étude sectorielle en patrimoine. Redéploiement du CUSM, Site de la Montagne - Beaupré, Pierre; Michaud, Josette (2006)
Keywords: Hôpitaux; Mont Royal; Royal Victoria Hospital

Entre voisins. La société paroissiale en milieu urbain: Saint-Pierre-Apôtre de Montréal, 1848-1930 - Ferretti, Lucia (Boréal, 1992)
Keywords: Communautés religieuses; Oblats de Marie-Immaculée; Saint-Pierre-Apôtre (paroisse)

Faubourg Québec: la ville conviviale - Dufaux, François (Continuité, 2000)
Keywords: Centre-sud (quartier); Faubourgs; Logement; Quartiers

Une culture matérielle riche dans le « Red Light » de Montréal: Inventaire et fouille archéologiques au faubourg Saint-Laurent MTL03-25-3, MTL03-25-2 et BjFj-121, 2003: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2005)
Keywords: Faubourgs; Logement; Quartiers; Saint-Laurent (quartier)

Chronique de l'industrie de la chaussure dans Hochelaga-Maisonneuve - Carrera, Jose David (D'une trac à l'autre, 1990)
Keywords: Artisans; Chaussure; Hochelaga (quartier); Maisonneuve; Quartiers; Travail

Italian Influences on the Cultural Life of Old Montreal - Goggio, Emilio (Canadian Modern Language Review, 1952)
Keywords: Italiens; Quartiers; Vieux-Montréal

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Keywords: Famille; Logement; Quartiers; Rosemont

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

Évolution du patrimoine architectural religieux du territoire historique de la Pointe-aux-Trembles - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2012)
Keywords: Patrimoine; Pointe-aux-Trembles; Quartiers; Églises

Les sociétés secrètes à l'œuvre dans l'histoire de la Pointe-aux-Trembles - Desjardins, Pierre (Atelier d'histoire de la Pointe-aux-Trembles, 2010)
Keywords: Clubs; Francs-Maçons; Pointe-aux-Trembles; Quartiers

Extrait de la vie domestique d'une famille de cultivateur et d'artisan du faubourg Saint-Louis, 1745-1825, site Viger, Montréal - Laliberté, Monique (Société d'archéologie et de numismatique de Montréal, 1986)
Keywords: Artisans; Famille; Faubourgs; Quartiers; Saint-Louis

Un territoire à habiter et à aménager (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Keywords: Ahuntsic; Cartierville; Logement; Quartiers; Sault-au-Récollet

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

L'architecture du Plateau Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
Keywords: Carmélites; Communautés religieuses; Logement; Plateau Mont-Royal; Quartiers; Églises

Alimentation, commerce et patrimoine: documenter les acteurs du Vieux-Montréal victorien 1850-1880 - Burgess, Joanne (Laboratoire d'histoire et de patrimoine de Montréal, 2016)
Keywords: Alimentation; Commerce de détail; Magasins; Patrimoine; Quartiers; Vieux-Montréal

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (Études d'histoire du Québec / Studies on the History of Quebec, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."--
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

"Ils ne sont plus le peuple qu’ils étaient hier": la culture ouvrière à Montréal-Est au moment de la Confédération - Petitclerc, Martin; Bellavance, Claude; St-Hilaire, Marc (Le fait urbain, 2020)
Keywords: Cartier, Georges-Étienne; Lanctôt, Médéric; Montréal-Est; Partis politiques; Quartiers; Rouges; Saint-Jacques; Saint-Louis; Sainte-Marie; Travail; Élections